The Influence of Work-Life Balance and Job Satisfaction on Employee Performance at the Administrative Division of the Data and Information Center, Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) - Syarif, Naufal Thafhan; Hasan, Diana (International Journal of Science and Society, 2025)
This study aims to examine the effects of work-life balance and job satisfaction on employee performance at the Data and Information Center (Pusdatin) of the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). Specifically, the study investigates: (1) the individual impact of work-life balance on employee performance, (2) the individual impact of job satisfaction on employee performance, and (3) the combined impact of work-life balance and job satisfaction on employee performance. Utilizing a quantitative method, the research draws on both primary and secondary data collected from a population of 70 administrative staff members. Data were gathered through questionnaires and observations, employing a saturated sampling technique. Validity and reliability tests confirmed that all items were valid and reliable, with the data also meeting assumptions of normality and the absence of multicollinearity. The findings reveal that work-life balance alone does not significantly affect employee performance, whereas job satisfaction has a significant individual effect. However, when combined, work-life balance and job satisfaction exert a significant and positive influence on employee performance.